Student Response to the Use of Augmented Reality Media in the Circulatory System in Humans - Asnah M. N. Limbong; Dewi A. P. Putri; Mujiono; Memet Casmat; Imelda Paulina Soko (Postgraduate, University of Mataram, 2023)
This study aims to explore the students' response to the use of Augmented Reality (AR) media in learning the circulatory system in humans. Until now, students have relied on textbooks consisting of pictures and text as their learning source. However, they face difficulties when studying topics such as the circulatory system that require complex visualization. A survey method was employed to collect data from students of the Biology Study Program at IPB University. The research sample consisted of 20 randomly selected respondents. The survey was conducted using a structured questionnaire designed to gather information about student engagement, conceptual understanding, interest, and preferences in using AR learning media. The questionnaire included questions about the respondents' response to their experience using AR media, perceived benefits, difficulties encountered, and suggestions for the development of future AR media. The collected survey data was analyzed using descriptive statistical methods. Descriptive statistics were used to summarize and depict the distribution of students' responses to the use of AR media in learning the circulatory system in humans. The results of this study can be concluded that the use of AR media in learning the circulatory system in humans has shown great potential. The majority of students responded positively, finding the use of AR media visually appealing and easy to learn.